Analytical characterisation of 3D nano scale ultra-thin film surrounding gate MOSFET. (6th June 2022) - Agarwal, Aditya; Sharma, R.L.; Mani, Prashant
This research focuses on characterisation and development of a drain current model for a 3D nanoscale surrounding gate metal oxide semiconductor field-effect transistor (SG MOSFET). The expressions for transconductance and subthreshold swing were also obtained. The drain current modelling reflects enhanced current and suppressed output transconductance. The expression for threshold voltage is also taken in the current work. The various technology parameters were taken, and the work function difference has also been presented. The results show that the surrounding gate MOSFET device offers improved performance over other devices. Simulation results verified using 3DTCAD Silvaco device simulator.